2000
DOI: 10.1088/0954-0083/12/4/309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Conductive Polyaniline/Clay Hybrid System

Abstract: This paper presents the synthesis and characterization of polyaniline/montmorillonite hybrid polymer. Montmorillonite is a natural clay mineral. By an intercalative polymerization reaction the hybrid is synthesized. In our study, electron paramagnetic resonance (EPR) spectra were examined together with controls (PANI and clay) with the EPR signals from all the PANI/clay samples showing very high spin density (10 19 spins/g polymer). PANI/clay samples show g-values higher than that of pure PANI control. Dc cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…3c and 3d. The band at 1296 cm 21 for the simple mixture and PANI-ES, assigned as the stretching vibration of C-N (n(C-N)) as indicated by a thick arrow in Fig. 3b, is significantly shifted to 1311 cm 21 for the intercalated nanocomposite as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…3c and 3d. The band at 1296 cm 21 for the simple mixture and PANI-ES, assigned as the stretching vibration of C-N (n(C-N)) as indicated by a thick arrow in Fig. 3b, is significantly shifted to 1311 cm 21 for the intercalated nanocomposite as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…After the observation of PANI intercalation into Cu 21 exchanged silicates by Cloos et al in 1979, 19 a number of studies on the preparation, properties and applications of PANI/layered silicate nanocomposites were carried out. [10][11][12][13][14][20][21][22][23][24][25][26][27][28] Most recently, Yang and Chen reported the synthesis of PANI/ organically modified clay nanocomposites and found that more PANI chains are formed between interlayer spacings of the modified clay, especially for HOOC(CH 2 ) 11 NH 3 1 modified clay because the acidic HOOC(CH 2 ) 11 NH 3 1 ions residing between interlayer spacings provide a stronger driving force for the intercalation of aniline monomer. 29 Yeh et al reported that regardless of clay content, the synthesis of PANI/clay nanocomposites with exfoliated silicate layers of clay was realized and they investigated the effect of such nanocomposites on the corrosion protection of cold rolled steel (CRS) when compared with that of an emeraldine base of PANI using a series of electrochemical measurements of corrosion potential and polarization resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[59] Polyanilines can be hybridized with inorganic materials such as montmorillonite [75] and coated on the surface of inorganic particles [76] to improve the ER performance. Approaches to the fabrication of polyaniline-coated [77] or polypyrrole-coated [78] ceramic composite materials are available, and many polymer/inorganic composite ER materials are expected to have the advantages of both polymeric and inorganic ER materials.…”
Section: Polyanilines and Polypyrrolesmentioning
confidence: 99%
“…In the past few years, researchers have shown much interest, from both the solid-state scientific and inorganic chemical perspectives, in the study of the electrically conducting behavior of 'organo-inorganic' composite materials [19][20][21][22][23][24]. Special interest today is focused on composite systems having high conductivity at ambient and sub-ambient temperatures, since they find unique applications, such as for separators in high power, versatile and rechargeable lithium batteries.…”
Section: Introductionmentioning
confidence: 99%